2003
DOI: 10.1007/s000180300006
|View full text |Cite
|
Sign up to set email alerts
|

Circular proteoglycans from sponges: first members of the spongican family

Abstract: Species-specific cell adhesion in marine sponges is mediated by a new family of modular proteoglycans whose general supramolecular structure resembles that of hyalectans. However, neither their protein nor their glycan moieties have significant sequence homology to other proteoglycans, despite having protein subunits equivalent to link proteins and to proteoglycan monomer core proteins, and glycan subunits equivalent to hyaluronan and to the glycosaminoglycans of hyalectans. In some species, these molecular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 188 publications
(229 reference statements)
3
72
0
Order By: Relevance
“…The data used to calculate the F max were restricted to the last peak of the force curves to ensure that only single molecule self-interaction forces were taken into consideration. The striking supramolecular similarities with MAF clearly place DAF within the family of circular proteoglycans from sponges, the spongicans (15). This finding is consistent with the phylogenetic kinship of D. anchorata and M. prolifera; both of these species belong to the sponge order Ceractinomorpha (38).…”
Section: Aggregation Factor Of D Anchorata Has a Circular Pattern Ansupporting
confidence: 78%
See 3 more Smart Citations
“…The data used to calculate the F max were restricted to the last peak of the force curves to ensure that only single molecule self-interaction forces were taken into consideration. The striking supramolecular similarities with MAF clearly place DAF within the family of circular proteoglycans from sponges, the spongicans (15). This finding is consistent with the phylogenetic kinship of D. anchorata and M. prolifera; both of these species belong to the sponge order Ceractinomorpha (38).…”
Section: Aggregation Factor Of D Anchorata Has a Circular Pattern Ansupporting
confidence: 78%
“…Sites-Images of DAF acquired via high resolution AFM revealed a proteoglycan remarkably similar to the AF of the sponge M. prolifera (MAF) described elsewhere (8,14,15), which enabled us to trace parallels between their structures, compositions, and chemical behaviors. DAF has a sunburst-shaped core constructed by a ring, ϳ130 nm across, and radiating arms up to 190 nm in length (Fig.…”
Section: Aggregation Factor Of D Anchorata Has a Circular Pattern Anmentioning
confidence: 96%
See 2 more Smart Citations
“…Later studies revealed that the speciesspecific cell aggregation of the marine sponge Microciona prolifera is mediated by a proteoglycan-like aggregation factor (MAF). Hereby, the N-glycans of two functional domains of MAF, MAFp4 and MAFp3, play an essential role: (i) the MAFp4-bound 6-kDa glycan (known as g-6), which in a Ca 2+ -independent way adheres to cell surface receptors, and (ii) the MAFp3-bound 200-kDa glycan (known as g-200), which promotes cell adhesion via a Ca 2+ -dependent self-association process [2,3]. Specific monoclonal antibodies against purified MAF, called Block 1 and Block 2, could inhibit the Ca 2+ -dependent self-association process without interfering with the cell-binding activity.…”
Section: Introductionmentioning
confidence: 99%